A method and application of lithium replenishment for positive electrode of lithium-ion battery

By adding soluble redox medium as a catalyst to the electrolyte of the lithium-ion battery, the decomposition of the positive electrode lithium supplement agent is solved, and the problem of irreversible capacity loss of lithium-ion batteries during the first cycle is achieved, and the battery energy density and safety improvement are achieved.

CN116130809BActive Publication Date: 2025-04-25HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310204492.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-01-10
Filing Date
2023-03-06
Publication Date
2025-04-25
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

The irreversible capacity loss of existing lithium-ion batteries during the first cycle seriously affects the battery's energy density and service life, and the existing positive electrode lithium supplementation process has safety hazards and reduced energy density.

Method used

The method of promoting the decomposition of the positive electrode lithium supplement agent by electrolyte additives is adopted to prepare a lithium supplement positive electrode sheet by mixing the positive electrode active material, adhesive, conductive agent and positive electrode lithium supplement agent. The soluble redox medium is used as the electrolyte additive to promote the decomposition of the positive electrode lithium supplement agent with high specific capacity.

Benefits of technology

The lithium loss during supplementary negative polarization is achieved, the energy density of the battery is increased, the proportion of inactive materials is reduced, and the problems of battery capacity attenuation and energy density are avoided. At the same time, the operation is simple, the cost is low, and the lithium supplement effect is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116130809B_ABST
    Figure CN116130809B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of secondary batteries, and discloses a method and application of lithium replenishment for the positive electrode of a lithium-ion battery. Specifically, electrolyte additives are used to promote the decomposition of a positive electrode lithium replenisher to achieve the purpose of replenishing the lithium loss during the formation of the negative electrode, and a lithium replenishing positive electrode sheet is prepared by mixing a positive electrode active material, an adhesive, a conductive agent and a positive electrode lithium replenisher. This method is different from using a solid phase component as a catalyst to promote the decomposition of a lithium replenisher, which reduces the proportion of inactive materials in the battery, thereby increasing the energy density of the battery; and after lithium replenishment, the byproduct gas of the positive electrode lithium replenisher is extracted by negative pressure during the formation stage, which will not affect the structure and performance of the battery, and has the characteristics of low cost, simple operation and good lithium replenishment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and more specifically to a method and application of replenishing lithium at a positive electrode of a lithium ion battery. Background Art

[0002] Due to the rapid development of various electronic devices, the demand for high energy density lithium-ion batteries is increasing. The specific capacity of graphite anodes in existing lithium-ion battery systems cannot meet the demand for high energy density, and a new generation of anode materials needs to be developed. Silicon anode materials with a specific capacity of up to 3580mah / g have become candidates for the next generation of anodes. However, silicon-based materials have a high initial irreversible capacity during the first cycle, which seriously affects the energy density and service life of the battery. To address this problem, researchers and engineers use lithium supplementation to compensate for the irreversible capacity loss during the initial cycle.

[0003] At present, the most common lithium replenishment processes are divided into positive electrode replenishment and negative electrode replenishment. Negative electrode replenishment uses lithium powder and lithium foil to replenish the irreversible capacity loss of the negative electrode during the first cycle. However, lithium powder and lithium foil are highly reactive and sensitive to water, which will cause safety problems and require additional processing to match the current production line. The positive electrode replenishment process is to add a small amount of high-capacity lithium-containing oxides to the positive electrode, such as Li5FeO4, Li2O, Li2O2, Li3N, Li2C2O4 and other materials. These materials are irreversible during the first charge and discharge, and the excess lithium is used to replenish the lithium loss during the first discharge process. Among them, LiF, Li2CO3, Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6, Li2C6O6, Li2C3O3, Li5FeO4, Li2NiO2, Li2O, Li2O2, Li3N, Li2CO3, and Li2N4O2C2 are suitable lithium supplement reagents because of their high specific capacity and stability to water, which are compatible with the current positive electrode process. However, their high decomposition potential (~4.6V) limits their application. Patent CN201680091755 uses precious metals or transition metal oxides as solid-phase catalysts to catalyze the decomposition of Li2O2, but the solid-phase catalyst, as an inactive material, will catalyze the decomposition of the electrolyte, causing the battery capacity to decay, and the dissolution of transition metals will cause the battery capacity to decay. In addition, inactive substances will reduce the energy density of the battery. Summary of the invention

[0004] In view of this, the present invention provides a method for replenishing lithium in the positive electrode of a lithium-ion battery, which replenishes lithium by promoting the decomposition of a lithium replenisher using an electrolyte additive, so as to replenish the lithium loss during the formation of the negative electrode.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A method for replenishing lithium at the positive electrode of a lithium-ion battery, which utilizes an electrolyte additive to promote the decomposition of a positive electrode lithium replenisher to replenish lithium at the positive electrode of the lithium-ion battery; specifically, a positive electrode active material, a binder, a conductive agent and the positive electrode lithium replenisher are mixed to prepare a lithium replenishing positive electrode sheet;

[0007] Wherein, the positive electrode lithium supplement agent is at least one of LiF, Li2CO3, Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6, Li2C6O6, Li2C3O3, Li5FeO4, Li2NiO2, Li2O, Li2O2, Li3N, Li2CO3, and Li2N4O2C2;

[0008] The electrolyte additive is a soluble redox medium, specifically sulfide, sulfate, nitrate, iodide, bromide, nitrite or chloride, and the mass fraction of the electrolyte additive in the electrolyte is 0.001wt% to 10wt%.

[0009] Optionally, the electrolyte lithium salt of the electrolyte is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonate imide), and lithium bis(fluorosulfonate imide), and the molar concentration of the electrolyte lithium salt in the electrolyte is 1 to 3 mol / L;

[0010] The solvent of the electrolyte is a carbonate solvent, specifically a mixture of one or more of cyclic esters ethylene carbonate, propylene carbonate, fluoroethylene carbonate and linear esters dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0011] Optionally, the positive electrode active material is lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide or lithium nickel oxide.

[0012] Optionally, the electrolyte additive is at least one of potassium thiosulfate, sodium thiosulfate, lithium thiosulfate, potassium iodide, lithium iodide, sodium iodide, lithium nitrate, sodium nitrate, ferric nitrate, ferrous nitrate, magnesium nitrate, calcium nitrate, aluminum nitrate, zinc nitrate, copper nitrate, silver nitrate, tin nitrate, ammonium nitrate, lithium bromide, potassium bromide, sodium bromide, lithium nitrite, sodium nitrite, ferric nitrite, ferrous nitrite, magnesium nitrite, calcium nitrite, aluminum nitrite, zinc nitrite, copper nitrite, silver nitrite, tin nitrite, ammonium nitrite, potassium chloride, lithium chloride, and sodium chloride.

[0013] The present invention aims to promote the decomposition of a high-capacity positive electrode lithium replenisher by adding a small amount of additives to the electrolyte, so as to achieve the purpose of replenishing the negative electrode lithium loss during formation. The invention focuses on protecting the method of achieving positive electrode lithium replenishment through the electrolyte. The additives and positive electrode lithium replenishers selected and protected by this method can be used not only in the commercial carbonate electrolyte system, but also in other solvent systems, such as ether electrolyte system, phosphate electrolyte system, etc.

[0014] The present invention also requests the application of the above-mentioned method for replenishing lithium at the positive electrode of a lithium ion battery in a lithium ion battery or a lithium metal battery.

[0015] Specifically, it also includes: a spring piece, a gasket, a diaphragm and a negative electrode; wherein,

[0016] The material used for the negative electrode is natural graphite, artificial graphite, alloy negative electrode material, silicon oxide negative electrode material, silicon carbon material, silicon oxide / carbon material; the diaphragm is a single-layer polypropylene diaphragm.

[0017] It can be seen from the above technical solutions that, compared with the prior art, the method and application of replenishing lithium at the positive electrode of a lithium-ion battery provided by the present invention has the following excellent effects:

[0018] The present invention utilizes electrolyte additives to promote the decomposition of positive electrode lithium replenishers to achieve the purpose of replenishing lithium loss during negative electrode formation, and prepares lithium replenishing positive electrode plates by mixing positive electrode active materials, adhesives, conductive agents and positive electrode lithium replenishers. This method is different from using solid phase components as catalysts to promote the decomposition of lithium replenishers, reducing the proportion of inactive materials in the battery, thereby improving the energy density of the battery; and after lithium replenishment, the byproduct gas of the positive electrode lithium replenisher is extracted by negative pressure during the formation stage, which will not affect the structure and performance of the battery, and has the characteristics of low cost, simple operation and good lithium replenishment effect; as in the experimental example, lithium oxalate is selected as the positive electrode lithium replenisher. When charged to 4.5V, lithium oxalate is almost not decomposed in the electrolyte of the control group, while the experimental groups #1 and #2 with additives have lithium oxalate decomposition reaching 100%, and the reaction formula is Li2C2O4→2Li + +2CO2↑; while decomposing to provide a large amount of active lithium, the product carbon dioxide can be discharged when it is formed. No lithium supplement and inert components will remain in the positive electrode, which greatly improves the energy density of the battery pack.

[0019] Specifically, the present invention adopts a positive electrode lithium supplement and an electrolyte additive as a catalyst, which will not increase inactive substances and greatly improves the energy density of the battery; and the battery electrolyte described in the present invention is compatible with the current lithium ion battery process technology, can better reduce the decomposition potential of the lithium supplement, reduce damage to the structure of the positive electrode active material, reduce the oxidative decomposition of the electrolyte, and improve the battery cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 The cycle performance curves of lithium oxalate half-cells prepared with the experimental group and control group electrolytes in Example 1 are shown in FIG.

[0022] Figure 2 This is the cycle performance curve of the lithium oxalate half-cell of Example 2.

[0023] Figure 3 This is the cycle performance curve of the lithium oxalate half-cell of Example 3.

[0024] Figure 4 This is the cycle performance curve of the lithium oxalate half-cell of Example 4.

[0025] Figure 5 This is the performance comparison curve of lithium nickel cobalt manganese oxide / / silicon carbon full battery under no lithium supplementation and lithium supplementation conditions. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The electrolyte prepared by the present invention is compatible with the current lithium ion battery process technology, and can better reduce the decomposition potential of the lithium supplement agent, reduce the damage to the structure of the positive electrode active material, reduce the oxidative decomposition of the electrolyte, and improve the battery cycle stability.

[0028] Example 1

[0029] In an argon glove box with oxygen and water pressures less than 0.1 ppm, the standard electrolyte was prepared as follows: lithium salt: 1.0 mol·L -1 Lithium hexafluorophosphate; organic solvent: a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, as a control group;

[0030] Additives: 1wt% potassium iodide were added to the reference electrolyte, and the obtained electrolyte was used as the experimental group;

[0031] Heat and stir at 40 °C in an argon glove box for 0.5 h until the potassium iodide is completely dissolved;

[0032] The electrolyte is used for half-cell testing with lithium metal as the negative electrode and lithium oxalate as the positive electrode, and a single-layer polypropylene film as the separator. The first cycle charge and discharge curve at 0.1C (1C = 200mAh / g) is as follows: Figure 1 The specific capacity of the experimental group reached 460.6 mAh / g when charged to 4.4 V, and 534 mAh / g when charged to 4.5 V, with 100% decomposition of lithium oxalate (theoretical specific capacity of lithium oxalate 525 mAh / g). The specific capacity of the control group was 2.3 mAh / g, with almost no decomposition of lithium oxalate.

[0033] Example 2

[0034] In an argon glove box with oxygen and water pressures less than 0.1 ppm, the standard electrolyte was prepared as follows: lithium salt: 1.0 mol·L -1 Lithium hexafluorophosphate; organic solvent: a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, as a control group;

[0035] Additives: 1wt% sodium bromide were added to the reference electrolyte, and the obtained electrolyte was used as the experimental group;

[0036] The mixture was heated and stirred at 40 °C in an argon glove box for 0.5 h until the sodium bromide was completely dissolved.

[0037] The electrolyte is used for half-cell testing with lithium metal as the negative electrode and lithium oxalate as the positive electrode, and a single-layer polypropylene film as the separator. The first cycle charge and discharge curve at 0.1C (1C = 200mAh / g) is as follows: Figure 2 When charged to 4.4V, the specific capacity reaches 365mAh / g, and when charged to 4.5V, the specific capacity reaches 531mAh / g, and the lithium oxalate is decomposed 100%.

[0038] Example 3

[0039] In an argon glove box where the oxygen pressure and water pressure were both less than 0.1 ppm, the electrolyte was prepared as follows: lithium salt: 1.0 mol·L -1 Lithium hexafluorophosphate; organic solvent: ethylene carbonate: dimethyl carbonate = 3:7 (volume ratio);

[0040] Additives: 1wt% sodium chloride were added to the reference electrolyte, and the obtained electrolyte was used as the experimental group;

[0041] The mixture was heated and stirred at 40°C in an argon glove box for 0.5 h until all the sodium chloride was dissolved.

[0042] The electrolyte is used for half-cell testing with lithium metal as the negative electrode and lithium oxalate as the positive electrode, and a single-layer polypropylene film as the separator. The first cycle charge and discharge curve at 0.1C (1C = 200mAh / g) is as follows: Figure 3When charged to 4.5V, the specific capacity was 482mAh / g, and the lithium oxalate was decomposed by 88.4%.

[0043] Example 4

[0044] In an argon glove box where the oxygen pressure and water pressure were both less than 0.1 ppm, the electrolyte was prepared as follows: lithium salt: 1.0 mol·L -1 Lithium dioxalatoborate; organic solvent: ethylene carbonate: dimethyl carbonate = 1:1 (volume ratio); additive: 1 wt % potassium nitrite, heated and stirred at 40° C. in an argon glove box for 0.5 h until the potassium nitrite is completely dissolved.

[0045] The electrolyte is used for half-cell testing with lithium metal as the negative electrode and lithium oxalate as the positive electrode, and a single-layer polypropylene film as the separator. The first cycle charge and discharge curve at 0.1C (1C = 200mAh / g) is as follows: Figure 4 When charged to 4.5V, the specific capacity was 283mAh / g, and the lithium oxalate was decomposed by 52%.

[0046] Experimental example

[0047] Select LiNi 0.83 Co 0.07 Mn 0.1 O2 (NCM) was used as the positive electrode, silicon carbon as the negative electrode, and the electrolyte was 1.0 mol·L-1 lithium hexafluorophosphate; the organic solvent was ethylene carbonate: dimethyl carbonate = 3:7 (volume ratio). The assembled full battery was used as the control group, denoted as #0;

[0048] Select LiNi 0.83 Co 0.07 Mn 0.1 O2+lithium oxalate is used as the positive electrode, wherein lithium oxalate accounts for 3% of the positive electrode mass, silicon carbon is used as the negative electrode, and the electrolytes in Examples 1 to 4 are used to assemble full batteries as experimental groups, which are respectively recorded as #1, #2, #3, and #4; single-layer polypropylene film is used as the diaphragm, the working voltage range is 2.5 to 4.3V, and the cycle diagram at 0.5C (1C = 200mAh / g) after 3 cycles of formation is as follows Figure 5 The performance comparison is shown in the following table.

[0049] Experiment number <![CDATA[4 th Specific Capacity]]> <![CDATA[100 th Specific Capacity]]> <![CDATA[4 th Specific capacity improvement]]> <![CDATA[100 th Specific capacity improvement]]> #0 162.5mAh / g 103mAh / g #1 197.5mAh / g 138.6mAh / g 21.6% 34.6% #2 197.3mAh / g 138.8mAh / g 21.4% 34.8% #3 177.5mAh / g 111.8mAh / g 9.2% 8.5% #4 177.5mAh / g 114.7mAh / g 9.2% 11.3%

[0050] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for replenishing lithium in a positive electrode of a lithium-ion battery, characterized in that: A method of using electrolyte additives to promote the decomposition of a positive electrode lithium replenisher to replenish lithium at the positive electrode of a lithium-ion battery; specifically, a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenisher are mixed to prepare a lithium replenishing positive electrode sheet; Wherein, the positive electrode lithium supplement agent is at least one of LiF, Li2CO3, Li2C4O4, Li2C2O4, Li2C3O5, Li2C5O5, Li2C4O6, Li2C6O6, Li2C3O3, Li5FeO4, Li2NiO2, Li2O, Li2O2, Li3N, Li2CO3, and Li2N4O2C2; The electrolyte additive is a soluble redox medium, specifically sulfide, sulfate, nitrate, iodide, bromide, nitrite or chloride, and the mass fraction of the electrolyte additive in the electrolyte is 0.001wt% to 10wt%.

2. The method for replenishing lithium at the positive electrode of a lithium-ion battery according to claim 1, characterized in that: The electrolyte lithium salt of the electrolyte is at least one of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonate imide), and lithium bis(fluorosulfonate imide), and the molar concentration of the electrolyte lithium salt in the electrolyte is 1 to 3 mol / L; The solvent of the electrolyte is a carbonate solvent, specifically a mixture of one or more of cyclic esters ethylene carbonate, propylene carbonate, fluoroethylene carbonate and linear esters dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

3. The method for replenishing lithium in the positive electrode of a lithium-ion battery according to claim 1, characterized in that: The positive electrode active material is lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide or lithium nickel oxide.

4. The method for replenishing lithium at the positive electrode of a lithium-ion battery according to claim 1, characterized in that: The electrolyte additive is at least one of potassium thiosulfate, sodium thiosulfate, lithium thiosulfate, potassium iodide, lithium iodide, sodium iodide, lithium nitrate, sodium nitrate, ferric nitrate, ferrous nitrate, magnesium nitrate, calcium nitrate, aluminum nitrate, zinc nitrate, copper nitrate, silver nitrate, tin nitrate, ammonium nitrate, lithium bromide, potassium bromide, sodium bromide, lithium nitrite, sodium nitrite, ferric nitrite, ferrous nitrite, magnesium nitrite, calcium nitrite, aluminum nitrite, zinc nitrite, copper nitrite, silver nitrite, tin nitrite, ammonium nitrite, potassium chloride, lithium chloride, and sodium chloride.

5. Use of the method for replenishing lithium in a positive electrode of a lithium ion battery as claimed in claim 1 in a lithium ion battery or a lithium metal battery.

6. The use according to claim 5, characterized in that: Also includes: Shrapnel, gasket, diaphragm and negative electrode; wherein, The material used for the negative electrode is natural graphite, artificial graphite, alloy negative electrode material, silicon oxide negative electrode material, silicon carbon material, silicon oxide / carbon material; the diaphragm is a single-layer polypropylene diaphragm.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN110100335A

  • Carbon-coated aluminum foil containing lithium-supplementing additive and preparation method of carbon-coated aluminum foil

    CN110444728A

  • Lithium ion battery

    CN112490490A